The Domestic and Global Impact of Japan's Policies for Growth - Batini, Nicoletta; N'Diaye, Papa.; Rebucci, Alessandro (Washington, D.C. : International Monetary Fund, 2005)
Japan is facing a sizable fiscal imbalance against a backdrop of weak trend growth and growing external imbalances in the world economy. This paper examines the possible impact of fiscal adjustment and productivity-enhancing structural reforms on the Japanese and world economies. Simulation results indicate that these could reduce substantially Japan's fiscal imbalance with only limited spillovers to the rest of the world. Specifically, faster productivity growth would help lower Japan's debt and limit the tendency of fiscal consolidation to increase the external surplus. In fact, very rapid productivity growth could potentially lead to a decline in Japan's external surplus and thereby have a positive effect on global imbalance. The modest extent of the spillovers to the rest of the world reflect the small size of the shocks and the diminished size of Japan in the world economy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet